Unmet need for family planning among reproductive-age women living with HIV in Ethiopia: A systematic review and meta-analysis. - Bereket Kefale; Bezawit Adane; Yitayish Damtie; Mastewal Arefaynie; Melaku Yalew; Assefa Andargie; Elsabeth Addisu (PLoS ONE, 2021)
Background Closing the gap of unmet for family planning is crucial to eliminate new pediatric HIV infections likewise to improve maternal and child health among reproductive-age women living with HIV. However, studies conducted on unmet need for family planning among reproductive-age women living with HIV showed inconsistent and non-conclusive findings on the magnitude of the problem. Moreover, there was no meta-analysis conducted in this area. So this systematic review and meta-analysis were conducted to estimate the pooled prevalence unmet need for family planning among reproductive-age women living with HIV in Ethiopia. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline was followed to review both published and unpublished studies in Ethiopia. All studies in PubMed, Cochrane Library, Hinari, Google Scholar, CINAHL, and Global Health databases were searched. Meta-analysis was performed using STATA 14 software. The heterogeneity and publication bias were assessed using the I2 statistics and Egger regression asymmetry test, respectively. Forest plots were used to present the pooled prevalence with a 95% confidence interval (CI). Results This review included 7 studies, and 3333 study participants. The pooled prevalence of unmet need for family planning among reproductive-age women living with HIV in Ethiopia was 25.13% (95%CI: 19.97, 30.29). The pooled prevalence of unmet need for spacing and limiting was 13.91% (95%CI: 10.11, 17.72) and 9.11% (95%CI: 6.43, 11.78), respectively. Conclusions One-fourths of reproductive-age women living with HIV had an unmet need for family planning. A variety of programmatic investments are needed to achieve more meaningful progress toward the reduction of unmet need for family planning among reproductive-age women living with HIV.